Controle vetorial de um motor de indução trifásico aplicado em sistemas de posicionamento - Araújo, Amanda Guerra de (2011)
This work consists of developing a system for position control of a three phase induction motor for positioning systems, using the technique of vectorial control in quadrature with the rotor flux. Several applications make use of this control, such as robot manipulators for welding and painting machines, tables and positioners coordinates in general. For a long time the machine most used in these systems was the DC for its simplicity of control, until the vector techniques were developed and improved, and significant advances in the power electronics allowing a drive high performance and lower cost using AC machines. To implement the drive with variable speed the asynchronous machine should be powered from a three-phase voltage source with variable frequency and amplitude, this source is obtained by static converters. The converter employed in this work uses the configuration with three arms, each containing two keys with controlled trigger and block, with one arm for each motor phase. A digital signal processor (DSP) was used to receive signals of voltage, current, position and generate the pulse width modulation (PWM).